1996
DOI: 10.1007/bf00353927
|View full text |Cite
|
Sign up to set email alerts
|

Homogenisation and oxygen transfer rates in large agitated and sparged animal cell bioreactors: Some implications for growth and production

Abstract: Because of concern for cell damage, very low agitation energy inputs have been used in industrial animal cell bioreactors, typical values being two orders of magnitude less than those found in bacterial fermentations. Aeration rates are also very small. As a result, such bioreactors might be both poorly mixed and also unable to provide the higher oxygen up-take rates demanded by more intensive operation. This paper reports experimental studies both of K( L ) a and of mixing (via pH measurements) in bioreactors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 10 publications
2
54
0
Order By: Relevance
“…However, as long ago as 1968, Kilburn and Webb (1968) showed that Pluronic F 68 (a block co-polymer of propylene oxide and ethylene oxide) was effective in decreasing cell damage. Such effectiveness was subsequently shown in many of the above studies, involving both stirred (Oh et al 1989(Oh et al , 1992Kioukia et al 1996;Nienow et al 1996) and bubble column bioreactors (Handa-Corrigan et al 1989;Kioukia et al 1992;Meier et al 1999).…”
Section: Due To Agitation Alonementioning
confidence: 84%
“…However, as long ago as 1968, Kilburn and Webb (1968) showed that Pluronic F 68 (a block co-polymer of propylene oxide and ethylene oxide) was effective in decreasing cell damage. Such effectiveness was subsequently shown in many of the above studies, involving both stirred (Oh et al 1989(Oh et al , 1992Kioukia et al 1996;Nienow et al 1996) and bubble column bioreactors (Handa-Corrigan et al 1989;Kioukia et al 1992;Meier et al 1999).…”
Section: Due To Agitation Alonementioning
confidence: 84%
“…Thus, this paper is relevant to both pH reduction due to CO 2 and to pH homogeneity and covers the experimental simulation of pH excursions as a result of alkali addition. It complements recent flow visualization of such phenomena (Nienow et al, 1996), the geometry and operating conditions here being very similar and based on the industrial-scale 8-m 3 bioreactors used by The Wellcome Foundation (now Glaxo Wellcome) (Langheinrich et al, 1998).…”
Section: Introductionmentioning
confidence: 85%
“…Aeration rates, because of the low oxygen demand of the current cell lines, are also very small (Nienow et al, 1996). Thus, the typical large animal cell bioreactor (Nienow et al, 1996) of 2-m diameter, T 200 , and of 8-m 3 in volume, V, when operated up to a liquid height, H (m), of H ‫ס‬ 1.3T, was agitated by a Rushton turbine of diameter, D (m), of 0.225T which is very small compared with the usual configuration of D ‫ס‬ 0.33T. The impeller was also positioned rather low in the vessel with a clearance, C (m), from the base C ‫ס‬ 0.225T rather than C ‫ס‬ 0.33T which is usually used and the agitator speed was a maximum of 1 s −1 if used continuously.…”
Section: Equipment and Measurement Techniquesmentioning
confidence: 99%
See 2 more Smart Citations